ENFORCEMENT OF HEALTH LAW IN THE CRISIS PERIOD OF PANDEMIC OUTBREAK COVID-19: â€œTHE POLICY OF LARGE SCALE SOCIAL LIMITATION (LSSL) IN INDONESIA VIEWED OF THE THEORY OF AL-MAQAASHID ASY-SYARâ€™IYYAHâ€ - Hidayatullah, Hidayatullah; Nasrullah, Nasrullah (Syariah: Jurnal Hukum dan Pemikiran, 2020)
AbstractStarting from the outbreak of the Corona Virus pandemic (Covid-19) in the early 2020s including in Indonesia, humanity was shaken with a variety of panic. To cope with the Covid-19 pandemic outbreak, the Government of Indonesia established a public health emergency status and adopted a Large Scale Social Restrictions (LSSL) policy. However, this health law enforcement issues a new polemic for the society, for Indonesian Muslims who cannot worship in congregation in mosques or other places of worship. The purpose of this study is to analyze the LSSL Policy that implemented by the government from the perspective of al-Maqashid asy-Syar?iyyah. This research is a legal research with literature study method and normative juridical research. Thus, the legal material related to the LSSL policy imposed by the Government of Indonesia. Based on the results of the study showed that there are some differences and their consequences, but the theory of al-Maqashid asy-Syar?iyyah LSSL policy is one of the best choices in the framework of overcoming the Covid-19 pandemic outbreak in Indonesia.Keywords: Health Law, LSSL, Pandemic outbreak, Covid-19, Maqashid Syar?iyyah. AbstrakBeranjak dari mewabahnya pandemi Virus Corona (Covid-19) pada awal tahun 2020 termasuk di Indonesia, membuat umat manusia digoncang dengan berbagai kepanikan. Untuk menanggulangi wabah pandemi Covid-19, Pemerintah Indonesia menetapkan status kedaruratan kesehatan masyarakat dan memberlakukan kebijakan Pembatasan Sosial Berskalaa Besar (PSBB). Namun penegakan hukum kesehatan ini mengakibatkan polemik baru bagi masyarakat, terutama bagi kaum muslimin Indonesia yang tidak bisa beribadah secara berjamaah di masjid atau tempat ibadah lainnya. Tujuan penelitian ini untuk menganalisa kebijakan PSBB yang diterapkan Pemerintah dari sudut pandang al-Maqashid asy-Syar?iyyah. Penelitian ini merupakan penelitian hukum dengan metode studi kepustakaan dan dengan pendekatan yuridis normatif. Dengan demikian, yang menjadi bahan hukum adalah regulasi terkait kebijakan PSBB yang diberlakukan oleh Pemerintah Indonesia. Adapun hasil penelitian menunjukan bahwa meskipun memiliki berbagai dampak dan konsekuensinya, namun secara teori al-Maqashid asy-Syar?iyyah kebijakan PSBB merupakan salah satu pilihan terbaik dalam rangka penanggulangan wabah pandemi Covid-19 di Indonesia.Kata Kunci: Hukum Kesehatan, PSBB, Wabah Pandemi, Covid-19, al-Maqashid asy-Syar?iyyah.